Perspectives from Nurse Managers on Informatics Competencies - Li Yang; Dan Cui; Xuemei Zhu; Qiuli Zhao; Ningning Xiao; Xiaoying Shen (The Scientific World Journal)
Background and Purpose. Nurse managers are in an excellent position for providing leadership and support within the institutions they serve and are often responsible for accessing information that is vital to the improvement of health facility processes and patients’ outcomes. Therefore, competency in informatics is essential. The purposes of this study are to examine current informatics competency levels of nurse managers and to identify the variables that influence these competencies. Methods. A questionnaire designed to assess demographic information and nursing informatics competency was completed by 68 nurse managers. Multiple linear regression analysis was conducted to analyze the factors influencing informatics competency. Results. Descriptive analysis of the data revealed that informatics competency of these nurse managers was in the moderate range 77.65±8.14. Multiple linear regression analysis indicated that level of education, nursing administration experience, and informatics education/training were significant factors affecting competency levels. Conclusion. The factors identified in this study can serve as a reference for nurse managers who were wishing to improve their informatics competency, hospital administrators seeking to provide appropriate training, and nursing educators who were making decisions about nursing informatics curricula. These findings suggest that efforts to enhance the informatics competency of nurse managers have marked potential benefits.